2019
DOI: 10.18632/oncotarget.24111
|View full text |Cite
|
Sign up to set email alerts
|

Association study of apelin-APJ system genetic polymorphisms with incident metabolic syndrome in a Chinese population: a case-control study

Abstract: Objectives: Apelin-APJ system has been implicated in the regulation of metabolic homeostasis. This study aimed to explore the genetic predisposition of the apelin-APJ system to metabolic syndrome. Materials And Methods: 1005 subjects were enrolled, including 448 metabolic syndrome patients and 557 controls. Seven single nucleotide polymorphisms, including rs909656, rs5975126, and rs3115757 of the apelin gene and rs7119375, rs10501367, rs9943582 and rs11544374 of the APJ gene, were genotyped.Results: For males,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“… 77 The risk alleles include Apelin rs3115757C, rs56204867C, and rs3761581A. 78 Beside polymorphisms, in vitro functional assays viz luciferase assay and real-time PCR, revealed allele-specific transcriptional regulation of apelin/APJ pathway by TFs such as TF specificity protein 1 (SP1). 79 Likewise, electrophoretic mobility shift assay and chromatin immunoprecipitation confirmed SP1 binding to the APLNR polymorphism rs9943582 (–154G/A), specifically to G allele and thereby upregulating its expression.…”
Section: Allele-dependent Control Of Apelin and No Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“… 77 The risk alleles include Apelin rs3115757C, rs56204867C, and rs3761581A. 78 Beside polymorphisms, in vitro functional assays viz luciferase assay and real-time PCR, revealed allele-specific transcriptional regulation of apelin/APJ pathway by TFs such as TF specificity protein 1 (SP1). 79 Likewise, electrophoretic mobility shift assay and chromatin immunoprecipitation confirmed SP1 binding to the APLNR polymorphism rs9943582 (–154G/A), specifically to G allele and thereby upregulating its expression.…”
Section: Allele-dependent Control Of Apelin and No Signalingmentioning
confidence: 99%
“…The apelin–APJ polymorphisms also were reported with low apelin 13 levels and the risk of hypertension 77 . The risk alleles include Apelin rs3115757C, rs56204867C, and rs3761581A 78 . Beside polymorphisms, in vitro functional assays viz luciferase assay and real‐time PCR, revealed allele‐specific transcriptional regulation of apelin/APJ pathway by TFs such as TF specificity protein 1 (SP1) 79 .…”
Section: Allele‐dependent Control Of Apelin and No Signalingmentioning
confidence: 99%
“…Apelin treatment has been proven beneficial for conditions as diverse as hypertension, atherosclerosis, myocardial infarction, and other cardiovascular diseases (Zhou et al, 2016). Numerous studies have shown that APLN/APLNR polymorphisms are associated with the risk of several diseases such as hypertension, CAD, and diabetes mellitus (Nowzari et al, 2018;Wu et al, 2018;Zhang et al, 2019). Our results demonstrated that the T allele of the rs2235310 polymorphism and the C allele of the rs9943582 polymorphism were risk factors in the development of CHD.…”
Section: Discussionmentioning
confidence: 51%
“…The rs2281068 variant ( APLN gene) is associated with T2DM in the Chinese Han population [ 67 ], whereas the rs3115757 variant correlates with obesity among women in a Chinese population [ 68 ]. The receptor (encoded by the APLNR gene) to which apelin binds is expressed in the spleen, brain, placenta, and adipose tissues [ 69 ].…”
Section: Resultsmentioning
confidence: 99%